THE HUMANISTIC PERSPECTIVES AND THE PATRIARCHAL BELIEF IN REBECCA BY DAPHNE DU MAURIER - Novita, Amanda; Syamsudin, Oom Rohmah; Meidasari, Venny Eka (INFERENCE: Journal of English Language Teaching, 2024)
This research study aims to investigate and analyze the manifestation of the Humanistic Psychological Perspective and Patriarchal Belief in Daphne Du Maurier's novel, "Rebecca." Through this research, valuable insights on the issues of multifaced nature of human experiences will be provided, offering a lens through which readers and scholars can explore and appreciate the intricate interplay pf psychological perspectives and societal ideologies within literary works. By employing a qualitative research approach, the study adopts a naturalistic inquiry method, focusing on contextualizing, interpreting, and emphasizing developmental processes and patterns. The research findings reveal intriguing insights into the novel's character dynamics. In terms of the Humanistic Psychological Perspective, the data description demonstrates that the characters in "Rebecca" exhibit a clear alignment with Maslow's Hierarchy of Needs. Furthermore, the data description illuminates the prevalence of patriarchal beliefs throughout the narrative. The analysis brings attention to the societal norms and power dynamics that perpetuate patriarchal structures. By exploring the interactions and behaviors of the characters, this research study sheds light on the complex manifestations and consequences of patriarchal belief systems within the story.